Relationship between male age, semen parameters and assisted reproductive technology outcomes. (8th October 2020) - Kasman, Alex M.; Li, Shufeng; Zhao, Qianying; Behr, Barry; Eisenberg, Michael L.
Abstract: Background: Low semen quality often obligates the use of assisted reproductive technology; however, the association between semen quality and assisted reproductive technology outcomes is uncertain. Objectives: To further assess the impact of semen quality on assisted reproductive technology outcomes. Materials and Methods: A retrospective cohort study was carried out at a single academic reproductive medicine center (January 2012‐December 2018). Patients undergoing at least one assisted reproductive technology cycle utilizing freshly ejaculated spermatozoa from the male partner were included. We assessed the association between semen quality (as stratified based on WHO 5th edition criteria), paternal age (< or ≥40), and reproductive/perinatal outcomes. To evaluate the differences in assisted reproductive technology outcomes by semen parameters and age, generalized estimating equations were applied for rates of fertilization, pregnancy, implantation, miscarriage, live birth, blast formation, gestational age, and normal embryo biopsy. Results: A total of 2063 couples were identified who underwent 4517 assisted reproductive technology cycles. Average ages of the male and female partners were 39.8 and 37.7, respectively. Lower pregnancy rates were observed in cycles with lower sperm motility (ie <40%; 39.9% vs 44.1%) and total motile count (ie <9 million; 38.3% vs 43.5%). When examining only cycles utilizing Intracytoplasmic Sperm Injection, only a lower motility count was associated with a decline in pregnancy rate (39.1% vs 44.9%). No association was identified between semen quality and gestational age or birth weight. Paternal age was not associated with ART outcomes. However, among assisted reproductive technology cycles in women <40, aneuploidy rate was higher for older men ( P  < .001). In cycles with women >40, no association between aneuploidy and male age was identified. Discussion: Sperm motility is associated with pregnancy rates, while other semen parameters are not. In cycles in women <40, paternal age is associated with embryo aneuploidy rate. Conclusion: Paternal factors are associated with assisted reproductive technology outcomes, and future studies should explore mechanisms by which semen quality is associated with assisted reproductive technology outcomes.